Direct Measurement of Raman Scattering Tensor of Orientation‐Fixed Single Iodine Molecules. (21st May 2015) - Wang, Dingdi; Tang, Zikang
<x xml:space="preserve">Abstract</x> Raman spectroscopy is the most widely used noninvasive analytical technique. Apart from the fingerprint Raman frequency for identifying vibrational mode of certain functional groups, the Raman scattering tensor can also be used to determine the corresponding vibrational symmetry as well as the orientation of this functional group with respect to the rest of the molecule. For gaseous single molecules, only limited structural information can be obtained from Raman spectroscopy owing to their freely rotating and randomly oriented nature. Here, a method, for the first time, is developed to directly determine the Raman scattering tensor on orientation‐fixed single iodine molecules, which are confined inside the nano‐sized channels of zeolite AlPO4–11 (AEL) single crystal. The experimental results are in good agreement with theoretical predictions based on a density functional theory. The optical transparency and appreciable size of the crystal facilitate the Raman exploration and the 3D manipulation. It is also demonstrated that iodine molecules' orientations are randomly distributed inside the nano‐channels of AlPO4–5 (AFI) crystal, which indicates that by carefully choosing the relevant zeolite crystal, the big family of zeolites can be utilized as directing template database for orienting a large number of guest molecules to estimate their structures by polarized Raman spectroscopy.